Understanding reactions between water and steelmaking slags: Iron distribution, hydrogen generation, and phase transformations. (5th June 2022) - Li, Peng; Li, Xiangyang; Guo, Hongwei; Yan, Bingji; Chen, Dong; Zhao, Wei; Seetharaman, Seshadri
Abstract: Environmentally friendly energy harvesting can be achieved by the H2 O thermochemical treatment of steelmaking slags. Hot slag from steel manufacturing is used as a sacrificial material to produce H2 in a stream of steam. In parallel, this process enhances the magnetic properties of the slag, benefitting the Fe recovery. In this work, the occurrence states of different iron species in slags, as well as their reactivity and phase transformations in H2 O, were investigated. The results showed that Fe 2+ was mainly distributed in olivine (Ca, Fe, Mg, Mn)2 SiO4 when the basicity was low. As the basicity increased, a gradual enrichment of Fe 2+ in RO phase (divalent oxides solid solution, R = Fe, Mg, Mn etc.) was observed. In addition to steelmaking slags, the H2 O splitting reactions of synthetic model iron compounds, RO phase (Mg1–x Fex O, x = 0.36, 0.63, 0.77) and kirschsteinite (CaFeSiO4 ) were also tested. RO phase exhibited fast kinetics, with its activity proportional to the FeO content. Oxidation of the magnesia-rich RO phase resulted in the phase segregation of iron-depleted magnesiowüstite (Mg, Fedepleted )O and iron-rich spinel (Mg, Ferich )3 O4 . The H2 O splitting of CaFeSiO4 suffered from extremely low kinetics below 900 °C, which could be enhanced by raising the temperature. The H2 production capacity of steelmaking slags was strongly affected by the basicity, which improved when more Fe 2+ existed as RO phase rather than CaFeSiO4 . After oxidation in steam at 850 °C, the slag sample with a basicity of 1.83 produced 29.3 cm 3 ⋅g −1 material hydrogen at 850 °C for 60 min, with a conversion ratio of 80.1%. Graphical abstract: Image 1 Highlights: Higher basicity benefited the enrichment of Fe 2+ in wüstite solution rather than kirschsteinite. Kirschsteinite exhibited a poor activity towards H2 O splitting below 900 °C. The substitution of MgO in wüstite solution exhibited unfavorable kinetics of H2 generation. The phase transformations of different model iron compounds were clarified.